Bilimsel Kültürün Doğuşu Üzerine /Stephen Gaukroger, The Emergence of a Scientific Culture: Science and the Shaping of Modernity 1210-1685, Oxford: Oxford University Pres, 2006,563 s. - KENAN, SEYFİ (My University, 2008)
0
Keywords: Felsefe